1998
DOI: 10.1111/j.1572-0241.1998.00459.x
|View full text |Cite
|
Sign up to set email alerts
|

Terbinafine Hepatotoxicity: Case Report and Review of the Literature

Abstract: We report a patient who developed significant liver dysfunction following therapy with terbinafine. At the end of a 3 1/2-wk course of terbinafine, he developed progressive jaundice and pruritus. His serum bilirubin peaked at 30.9 mg/dl 3 wk after discontinuing terbinafine. A liver biopsy revealed mild to moderate mixed cellular infiltrate in the portal tracts, and hepatocellular and canicular cholestasis. His liver tests normalized 100 days after stopping terbinafine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 7 publications
0
13
0
1
Order By: Relevance
“…While the majority of cases resolve following discontinuation of terbinafi ne, reports are available detailing patients that have progressed to liver transplantation and death. 189,190 Notably, hepatic fi ndings are not restricted to adults. An FDA review of the recently marketed terbinafine oral granule identifi ed two cases, among 1042 children treated, of elevated transaminases leading to discontinuation of the drug.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…While the majority of cases resolve following discontinuation of terbinafi ne, reports are available detailing patients that have progressed to liver transplantation and death. 189,190 Notably, hepatic fi ndings are not restricted to adults. An FDA review of the recently marketed terbinafine oral granule identifi ed two cases, among 1042 children treated, of elevated transaminases leading to discontinuation of the drug.…”
Section: Adverse Effectsmentioning
confidence: 99%
“…Very recently, a systematic review and meta-analysis documented an overall incidence of 3.6%-4.2%, which may be considered as common [31] . Data on other antifungals such as terbinafine are more scant and mostly based on individual case reports [32][33][34] . The latest population-based study in Taiwanese concluded that oral antifungal agents are associated with a low incidence if DILI, which may be fatal (especially in the elderly) and increased for longer treatment [35] .…”
Section: Data Selection and Analysismentioning
confidence: 99%
“…Patient ages ranged from ‘young’1 to 75 years old 2. The typical symptoms of terbinafine-induced hepatotoxicity include marked and progressive pruritus, jaundice, malaise and anorexia 2 4 5. Typically, symptom onset is from weeks 3–6 of therapy but may peak after cessation of terbinafine 1 2 5…”
Section: Discussionmentioning
confidence: 99%